Profile of congenital rubella syndrome in Soetomo General Hospital Surabaya, Indonesia - Nyilo Purnami; Dionisia Vidya Paramita (MDPI AG, 2020)
Background: Definition of Congenital Ruben Syndrome (CRS): a disease caused by rubella virus infection. Routine surveil- lance of CRS is part of a government pro- gram in documenting the incidence of CRS so that infants with CRS are diagnosed promptly and receive appropriate care. Objective: This study aims to repodiology Outpatient General Hospital Dr. Soetomo Surabaya.Method: A descriptive study from CRS surveillance data for the period from January 1st until December 31rd, 2015. Data was from Infants who came to the Audiology Outpatient General Hospital Dr. Soetomo Surabaya and did hearing and serological examination. Results: A total of 65 infants were involved in surveillance. The highest num- ber of patients was the age group 1- <3 years (21 patients, 31.2%). A total of 36 patients (55.4%) were male, 45 babies (69.2%) were suspected of suffering from CRS with 2 infants (3.1%) classified as a laboratory-confirmed CRS. Hearing abnor- malities were found in 36 infants (55.4%). Bilateral hearing loss was found in 23 infants (35.4%) and unilateral in 13 infants (20%).Conclusions: This study shows that hearing impairment is the most common clinical symptom with most bilateral hear- ing loss. The supervision still needs to be continued to capture more CRS cases in the community and effective supervision to detect hearing impairment early.